2014
DOI: 10.1039/c3dt53433b
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous silica nanoparticles for enhancing the delivery efficiency of immunostimulatory DNA drugs

Abstract: We developed a potential immunostimulatory double-stranded DNA (dsDNA) delivery system by the binding of dsDNA to amino-modified mesoporous silica nanoparticles (MSNs) to form MSN-NH2/dsDNA complexes. Serum stability, in vitro cytotoxicity, cell uptake, and type I interferon-α (IFN-α) induction of MSN-NH2/dsDNA complexes were evaluated. The results showed that MSN-NH2 nanoparticles had no cytotoxicity to Raw 264.7 cells, and MSN-NH2/dsDNA complexes enhanced the serum stability of dsDNA due to the protection by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 46 publications
(69 reference statements)
1
35
0
Order By: Relevance
“…Some preliminary results have shown that the center‐radial large pore channels can rapidly and easily adsorb and release relatively large organic molecules, i.e., plasmid DNA (pDNA, M.W. = 4733 bp), bovine β‐lactoglobulin (molecular size: 3.78 × 4.96 × 5.65 nm), double‐stranded DNA (dsDNA), the poorly water‐soluble drug telmisartan, methylene blue, rhodamine B, doxorubicine . Zhao's group demonstrated that 3D‐dendritic MSNs exhibited an obvious advantage for loading and releasing large protein molecules compared with conventional MSNs owing to their adjustable large pore sizes (2.8–13 nm) and multigenerational pore structures.…”
Section: Applications Of Dendritic Silica Particles With Center‐radiamentioning
confidence: 99%
See 1 more Smart Citation
“…Some preliminary results have shown that the center‐radial large pore channels can rapidly and easily adsorb and release relatively large organic molecules, i.e., plasmid DNA (pDNA, M.W. = 4733 bp), bovine β‐lactoglobulin (molecular size: 3.78 × 4.96 × 5.65 nm), double‐stranded DNA (dsDNA), the poorly water‐soluble drug telmisartan, methylene blue, rhodamine B, doxorubicine . Zhao's group demonstrated that 3D‐dendritic MSNs exhibited an obvious advantage for loading and releasing large protein molecules compared with conventional MSNs owing to their adjustable large pore sizes (2.8–13 nm) and multigenerational pore structures.…”
Section: Applications Of Dendritic Silica Particles With Center‐radiamentioning
confidence: 99%
“…They could also be modifi ed with fl uorescent molecules or quantum dots, and used in cell ima ging. [ 53,55,57,66,70,95,96 ] To investigate the advantages of center-radial large pores and the combination of center-radial pores and uniform 2-4 nm mesopores, we employed uniform dendritic HPSN-NH 2 with small particle sizes (160-250 nm) and large center-radial pore sizes (10-120 nm) as supports to construct advanced delivery systems. [ 66 ] Short branched PEI (M.W.…”
Section: Biomedical and Biotechnological Applicationsmentioning
confidence: 99%
“…21 Several nanoparticles were used to stimulate the human cytokines such as interleukin-6 and interferon-. [22][23][24] The novel HfO 2 biosensor is constructed for early stage detection of human interleukin-10 to avoid heart failure. 25 HfO 2 surfaces are used for phosphate dependent, oriented immobilization of DNA for biosensing applications.…”
Section: Articlementioning
confidence: 99%
“…Both PCL and CS are biodegradable cationic polymers, which easily anchor onto surfaces of MCM-41, enhancing the biocompatibility and its presence on the structure of MCM-41, which did not affect the cellular viability as reported in [31,33].…”
Section: In Vitro Cellular Uptake Assaysmentioning
confidence: 99%
“…The results showed that in concentrations above 100 µg·mL −1 , the presence of APTES is toxic with 50% of viable cells. Other results report [33] using APTES modified nanoparticles to form dsDNA (double-stranded DNA) complexes, showing that even at a concentration above of 100 µg·mL −1 , the presence of APTES is not toxic with 80% of viable cells. Probably, the toxicity of APTES depends on the cell line.…”
Section: In Vitro Cellular Uptake Assaysmentioning
confidence: 99%